Enhancing Udeng Pacul Gowang Craftmen’s Business Through Technology: A Community Service Initiative in Wonoayu, Pagerngumbuk, Sidoarjo - Nurratri TR, Januari Pratama; Warmana, G. Oka; Sholihah, Dewi Deniaty (Nusantara Science and Technology Proceedings, 2023)
The Udeng craftsmen in Sidoarjo have traditionally adhered to rudimentary techniques and order-based marketing approaches to sustain their livelihoods. Conversely, in the contemporary digital era, the ubiquity of technology is undeniable. This academic paper elucidates the outcomes of a community service initiative aimed at elevating the udeng pacul gowang craftsmen in Wonoayu, Pagerngumbuk, Sidoarjo, by harnessing the potential of technology in their business endeavors. Furthermore, this community service comprises three principal activities, each firmly grounded in the corresponding theoretical framework of “pillars of a digital ecosystem for enterprises”. To commence, the community received training in the proficient management of digital-based financial record-keeping, facilitated through the utilization of an Android application known as "BukuKas." Subsequently, with regards to digital marketing, udeng craftsmen were taught the utilization of digital platforms such as WhatsApp for Business and Instagram for business purposes. Additionally, they were encouraged to develop their electronic product catalogs, thereby enhancing their proficiency in product photography. Lastly, udeng craftsmen were equipped with knowledge pertaining to cybersecurity, encompassing topics such as copyright protection and cybersecurity threats, including cyber scams. This comprehensive community service initiative contributes to the enhancement of financial literacy and the development of digital marketing capabilities among small and medium-sized enterprises. Moreover, this research aligns with the principles of community economic growth in accordance with Sustainable Development Goals, notably with a focus on promoting decent work and economic growth.